Modelagem matemática: uma abordagem do método gráfico e do método simplex na resolução de problemas de otimização - Barrios, Júlio César [UNESP] (2015)
One of the major issues faced by teachers in the classroom, when introducing a new subject, is having to answer the same question from the students: What's the reason for us to learn this?. Many times, teachers are not capable of making that kind of connection, and showing that to the students. It is already known that, in fact, not everything that is taught in school and not everything suggested on the Brazilian National Curriculum Parameters (PCN) are part of the students' everyday lives. Teachers have the task of motivating them, enthusiastically showing them the importance of mathematics; trying, as often as possible, to find a challenging situation, which teachers can use to support their work. In order for this to happen, Mathematical Modeling can be a great support system. It is a methodology alternative for the teaching of mathematics, and aims at interpreting and understanding the most different phenomena of our everyday lives. This study focuses on widely used topic in the fields of Economics, Business Administration, Engineering, and Finance, which are the optimization problems when several variables are shown for a given situation and the challenge is trying to reach the perfect solution. It is a subject in which high school students can be motivated to reflect and think about a given real situation, which, theoretically, could only be seen on higher education degrees. The mathematical tools that should be used for solving the problems are all studied by the students during high school: Matrices, Linear Systems of Equations and Inequalities, Functions, graphing in the Cartesian Plane, among others, and also there's the possibility of using technological resources during the process of solving the problem. The goal of this study is choosing challenging situations which involves the optimization of the problems, and trying to solve them according to the Graphic Method and the Simplex Method. A company profit maximization ...